2018
DOI: 10.1136/neurintsurg-2017-013699
|View full text |Cite
|
Sign up to set email alerts
|

Neuro Elutax SV drug-eluting balloon versus Wingspan stent system in symptomatic intracranial high-grade stenosis: a single-center experience

Abstract: The ElutaxDEB may be a promising alternative treatment for patients with symptomatic high-grade intracranial stenosis showing a significantly lower rate of ischemic re-events or restenosis in comparison with the WingspanStent-treated patients with a similar safety profile. Further studies will be needed to definitively elucidate the role of pDEB in the management of symptomatic intracranial high-grade stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 31 publications
3
44
1
Order By: Relevance
“…In addition, no complications with DCB-PTA occurred in that study 12. The results of the present study using the SeQuent Please NEO DCB system further support these observations.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, no complications with DCB-PTA occurred in that study 12. The results of the present study using the SeQuent Please NEO DCB system further support these observations.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study showed that Neuro Elutax SV, a specifically dedicated DCB for intracranial use, had similar effectiveness and lower restenosis rates than Wingspan stents in patients with symptomatic high-grade stenosis 12. In addition, no complications with DCB-PTA occurred in that study 12.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent research suggested that a paclitaxel DCB is a viable alternative to drug-eluting stents,17 with the added advantage of avoiding a permanent implant. The new advent of Neuro Elutax DCB further increased the feasibility of using a DCB in intracranial arteries 18. However, the application of a DCB has not been systematically explored for intracranial de novo atherosclerosis disease.…”
Section: Introductionmentioning
confidence: 99%
“…Case series demonstrated the technical feasibility and good results regarding angiographic recurrence rates also with respect to ICAS [47,48]. In a retrospective comparison, the paclitaxelcoated Elutax DEB (drug-eluting balloon) (Aachen Resonance, Aachen, Germany) even showed a clear superiority over the Wingspan stent with respect to clinical recurrence and angiographic restentosis rate [49]. In a retrospective comparison of two drugeluting stents (DES), 100 successful procedures showed a low restenosis rate of 3.6 % exclusively after treatment with zotarolimus-coated Resolute Integrity TM (Medtronic Inc., Santa Rosa, CA, USA), and in no single case after treatment using paclitaxelcoated Taxus Element TM (Boston Scientific Corporation, Natick, MA, USA).…”
Section: Drug-coated Balloons and Stentsmentioning
confidence: 93%